A Filter‐Based Motion Cueing Algorithm for a Redundant Driving Simulator. Issue 1 (17th December 2018) - Ellensohn, Felix; Breyer, Manuel; Schwienbacher, Markus; Venrooij, Joost; Rixen, Daniel
Abstract: A Motion Cueing Algorithm (MCA) determines the simulator's input subject to the driving dynamics demands. Main limitations form the technical restrictions of the simulator's actuators on position, velocity and acceleration level. This paper shows a filter‐based MCA for a redundant motion system exhibiting nine degrees of freedom (DoF). The redundant DoF are distributed by a frequency divider. A parameter optimization scheme is shown to estimate the unknown parameters of the MCA subject to the tilt restrictions and the exploitation of the actuators.